Planning Approval Process: An Analysis of Property Developers’ Experiences in Southwestern Nigeria (International Journal of Built Environment and Sustainability, 2022)
Globally, development control is one of the main activities of the planning agencies aimed at ensuring sustainable development in human settlements. Previous studies primarily explored compliance with planning regulations whereas issues of awareness, satisfaction, and willingness to participate have not been adequately dealt with. This study evaluates the property developers’ experiences with the planning approval process (PAP) in southwestern Nigeria. The specific objectives are to (i) probe property developers’ awareness of the legality of the PAP, (ii) examine property developers’ satisfaction levels regarding the PAP, (iii) determine property developers’ willingness to participate in PAP discourse, and (iv) examine problems associated with the PAP. Purposive and convenience sampling techniques were adopted to elicit data from 96 respondents using a structured questionnaire. Data were analyzed using both descriptive and inferential statistics. Major findings showed that 68.8% of the developers were aware of the legality of PAP, 70.8% expressed satisfaction with the PAP, and 78.1% were willing to participate in public discourse about PAP. Fishers’ Exact test revealed that the location of developers (χ2= 6.907, p=0.025) and gender (χ2= 0.000, p=0.023) were significantly associated with developers’ awareness of the legality of PAP. The Spearman Correlation test indicated a significant association between developers’ satisfaction with PAP and their support for seeking planning approval (r=0.339, p=0.001) as well as planning approval processing time (r=0.250, p=0.026). The study recommends aspects of PAP the planning agencies need to improve upon towards achieving sustainable PAP. The study outcome will be useful for policy formulation in areas of education and awareness creation, planning approval processing time, and procuring documents required by the planning agencies. Addressing these issues will mean property developers will derive greater satisfaction from planning agencies’ services and will be inspired to participate in planning matters.
Keywords: Development control, Physical planning, Planning approval process, Property developer, Nigeria